Association between body weight perception and actual body mass index among adult women in Erbil city, Iraq - Sherzad A. Shabu; Mariwan H. Saka; Manhal N. Boya; Hamdia M. Ahmed; Sahar M. Zaki; Florentina Hettinga; Nazar P. Shabila (BMC, 2024)
Abstract Background The misperception of body weight can significantly affect individuals' health behaviors, such as physical activity, diet, and weight management. This study aimed to examine the association between body weight perception and actual body mass index (BMI) among adult women and explore the factors influencing this relationship. Methods Five hundred forty female individuals aged 18-65 participated in this cross-sectional study. The validated Global Physical Activity Questionnaire was used for data collection. The BMI of the participants was calculated from measured body weight and height. Body weight perception was assessed using a single questionnaire item. The association of BMI and body weight perception was assessed, and the result was categorized as underestimation, consistency, and overestimation. The Chi-square test was used to assess the association between the consistency of BMI and body weight perception by different sociodemographic factors. The kappa test was used to analyze the consistency of BMI and body weight perception. Results Of the 540 participants, 13.3% underestimated their body weight status, 79.1% accurately perceived their body weight status, and 7.6% overestimated their body weight status. Unmarried women (11.7%) were more likely than ever married (4.3%) to overestimate their body weight (p = 0.005). On multiple logistic regression, being unmarried (OR = 1.68 (95%CI 1.01-2.80)) was significantly associated with body weight misperception. Body weight perception and BMI categories showed a significantly good consistency (kappa = 0.612, p < 0.001). Correct perception of body weight was highest among the overweight, followed by normal weight and underweight individuals (82.1%, 75.8%, and 72.2%, respectively). Conclusion Body weight perception was well associated with actual body weight status. Unmarried women are more likely to misperceive body weight, particularly overestimating it. Underestimation of body weight was relatively high and much higher than the overestimation, which might keep obese individuals from weight loss activities. Preventing obesity should include awareness about body weight misperceptions.